Talking to a (Segregation) Wall: Intergroup Contact and Attitudes Toward Normalization Among Palestinians From the Occupied Territories. Issue 1 (17th March 2022) - Albzour, Mai; Bady, Zacharia; Elcheroth, Guy; Penic, Sandra; Reimer, Nils; Green, Eva G. T.
Abstract : This article examines how Palestinians' intergroup contact experiences relate to their attitudes towards interactions with Israelis (i.e., normalization). We draw on four recent advances in intergroup contact literature. First, recent research indicates that positive contact can impede disadvantaged groups' motivation to challenge inequalities. Second, increased endorsement of normalization mediates this sedative effect of positive contact on motivation to resist in the West Bank. Third, negative contact has been related to increased motivation for social change. Fourth, institutions and societal norms shape the meaning of intergroup contact and its effect on intergroup relations. We hypothesize that negative experiences at checkpoints can act as reminders of institutionalized inequalities and thus attenuate sedative effects. Furthermore, we explore the contextual boundary conditions of such reminder effects. Analyses of cross‐sectional survey conducted among a representative sample ( N = 1, 000) in the West Bank including Jerusalem showed that (1) positive intergroup contact related to normalization endorsement (sedative effect), (2) negative intergroup contact related to decreased normalization endorsement (mobilizing effect), and (3) negative contact experiences (at checkpoints) canceled out the effect of positive contact (reminder effect), but only in Jerusalem. Results suggest that the impacts of intergroup contact need to be interpreted in light of institutionalized forms of group inequality and segregation.